The Effect of Funding Policy, Investment Policy, and Dividend Policy on the Firm Value through Good Corporate Governance as an Intervening Variable - Muhammad Sulhan; Puji Endah Purnamasari (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2020)
The company’s main objective is maximizing the firm value which means it increases shareholder prosperity. This can be achieved by combining funding policy, investment policy, and dividend policy optimally. The application of good corporate governance (GCG) is used to direct and control the company to be able to run the company’s operations following stakeholder’s expectations. This study aims to determine the influence of funding policies, investment policies, and dividend policies on firm value by using GCG as a mediating variable.This study uses a quantitative approach. In this study, the population is all companies listed in the banking sub-sector on the Indonesia Stock Exchange in 2013-2017, with a total of 43 companies. The samples are taken by purposive sampling technique with 12 companies. The method of data analysis used in this study was descriptive analysis and path analysis using Partial Least Square (SmartPLS3).The result of the study shows that the investment policy has a positive effect on firm value. The funding policy and dividend policy do not affect firm value. While investment policy has a positive effect on GCG. Furthermore, the funding policy and dividend policy do not affect GCG. GCG successfully mediates the relationship of investment policy with the firm value. That is, the higher profitability will affect the GCG so that it will affect the firm value. However, GCG as an intervening variable does not succeed in mediating the relationship of funding policy and dividend policy with the firm value.